1991
DOI: 10.1007/bf01850715
|View full text |Cite
|
Sign up to set email alerts
|

Antiovulatory action of anordrin in the cynomolgus monkey (Macaca fascicularis)

Abstract: Anordrin (2 alpha, 17 alpha-diethynyl-A-nor-5 alpha-androstane-2 beta, 17 beta-diol dipropionate) was studied for its antiovulatory potency in the cynomolgus monkey. Anordrin, administered daily on days 9-13 of the menstrual cycle in doses of 4.0 and 8.0 mg/kg body weight, did not inhibit luteal activity in the cycle in which it was given, but delayed the development of ovarian follicles for 5 to 6 months. When a single low dose (0.1 or 0.2 mg/kg b.w.) was administered during the first 3 days of the menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Mehta and Chatterton [ 36 ] investigated the anovulatory effect of Anordrin, a synthetic steroidal antiprogestin administered intramuscularly in sesame oil at variable doses. Mehta and Chatterton [ 36 ] discovered that a lower dose administered during the macaque menstrual cycle’s first three (3) days inhibited follicular development, which was manifested by delayed ovulation time. Furthermore, the findings of [ 36 ] contradict other findings, which report that women taking Anordrin as a postcoital contraceptive had anovulatory cycles [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mehta and Chatterton [ 36 ] investigated the anovulatory effect of Anordrin, a synthetic steroidal antiprogestin administered intramuscularly in sesame oil at variable doses. Mehta and Chatterton [ 36 ] discovered that a lower dose administered during the macaque menstrual cycle’s first three (3) days inhibited follicular development, which was manifested by delayed ovulation time. Furthermore, the findings of [ 36 ] contradict other findings, which report that women taking Anordrin as a postcoital contraceptive had anovulatory cycles [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mehta and Chatterton [ 36 ] discovered that a lower dose administered during the macaque menstrual cycle’s first three (3) days inhibited follicular development, which was manifested by delayed ovulation time. Furthermore, the findings of [ 36 ] contradict other findings, which report that women taking Anordrin as a postcoital contraceptive had anovulatory cycles [ 37 ]. However, this could be because they took the drug as early as their menstrual cycles, suggesting the reason for ovulation failure [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Luteolytic activity of anordrin has not been observed in the monkey, but anordrin has not been administered shortly after formation of the corpora lutea as it was in the rat. Nevertheless, when anordrin was given within the first 6 days of the menstrual cycle, it had a suppressive effect on progesterone production, measured as pregnanediol excretion, which was proportional to the dose administered [1]. The length of the primate luteal phase, however, was not altered by the treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in this laboratory have demonstrated that anordrin (2a,17a-diethynyl-A-nor-5a-androstane-2#,17#-diol dipropionate) and anordiol, the unesterified form, inhibit ovulation in the monkey when given as a single dose within the first 6 days of the menstrual cycle, that is, during the stage of follicular recruitment [1]. Further studies revealed that anordrin given once a month for 5 months starting on the first day of the menstrual cycle suppressed ovulation continuously for 7 -0.8 (SD) months [2].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies from this laboratory have shown that anordrin (anordiol dipropionate) and anordiol inhibit ovulation in the mature monkey [1,2] and rat [31. Biological and biochemical studies have shown that anordiol is a weak estrogen with antiestrogenic activity in the mature animal [3][4][5][6]. Tamoxifen (TA) is a non-steroidal triphenylethylene derivative with antiestrogenic activity.…”
Section: Introductionmentioning
confidence: 99%